2013
DOI: 10.1111/1365-2745.12063
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering multiscale effects of aridity and biotic interactions on the functional structure of Mediterranean shrublands

Abstract: Summary 1.Habitat filtering (HF, trait convergence) and niche differentiation (ND, trait divergence) are known to impact upon plant community structure. Both processes integrate individual responses to the abiotic environment and biotic interactions. Thus, it is difficult to clearly identify the underlying abiotic and biotic factors that ultimately impact community structure by looking at community-level patterns of trait divergence or convergence alone. 2. We used a functional trait-based and multiscale appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
186
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(212 citation statements)
references
References 85 publications
(166 reference statements)
17
186
1
8
Order By: Relevance
“…The trait variables obtained per species and mesocosm were normalized using a log-transformation to reduce the impact of species with extreme trait values. To represent each axis of variation, we selected one trait for each PCA component as a functional marker of specialization (Gross et al, 2013). We used a PCA for these analyses because different traits are associated with different niche axes (Butterfield & Suding, 2013), and to avoid selecting highly correlated traits for further analyses (Supporting information Table S3).…”
Section: Evaluating Functional Traits Variation Among Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The trait variables obtained per species and mesocosm were normalized using a log-transformation to reduce the impact of species with extreme trait values. To represent each axis of variation, we selected one trait for each PCA component as a functional marker of specialization (Gross et al, 2013). We used a PCA for these analyses because different traits are associated with different niche axes (Butterfield & Suding, 2013), and to avoid selecting highly correlated traits for further analyses (Supporting information Table S3).…”
Section: Evaluating Functional Traits Variation Among Plant Speciesmentioning
confidence: 99%
“…This response could be related to initial "sampling effect" (Tilman, Lehman, & Thomson, 1997); that is, treatments with higher species richness had higher probabilities of having keystone species. Alternatively, this response may have occurred during the experiment and may reflect an effect of biotic interactions (Gross et al, 2013). Since tall species are better competitors than short species for space, the latter can be outcompeted.…”
Section: Climate Change and Plant Species Richness Alter The Functimentioning
confidence: 99%
“…Here, we propose in future studies to consider multiple spatial scales in combination with the multi-dimensionality of traits to better associate trait patterns with assembling rules (see Gross et al 2013a, b as an example).…”
Section: Which Assembly Process For Which Conditions?mentioning
confidence: 99%
“…In addition to the former competition-based process of species stabilization, facilitation is also able to promote the coexistence of subordinate to rare species with dominant species within a community. For instance, Gross et al (2013a) observed that facilitation interplayed with an aridity gradient to enhance subordinate and rare species and the biodiversity of semi-arid Mediterranean shrublands. All together, niche-based processes may jointly operate in a given community promoting different statuses of species.…”
Section: Which Assembly Process For Which Status In the Community?mentioning
confidence: 99%
“…Different shrub assemblages, which are the result of long-term processes such as habitat filtering and niche differentiation (Gross et al, 2013), may exhibit contrasting colonization dynamics. Differences in life-history traits among species (e.g.…”
Section: Introductionmentioning
confidence: 99%